Auditoria ambiental de cumplimiento del relleno sanitario del cantón Machala. - Calle Veintimilla, Ginno Xavier (2012)
The purpose of this research is to suggest the change and implementation of those measures and actions that presented non-conformities both major and minor with the compliance of legal environmental parameters within the environmental management plan.